Promoting Sustainable Life through Education for Sustainable Development (ESD) and Religious Education - Fiana, Sari Okta; Fahrurrazi, Fahrurrazi (J-Lalite: Journal of English Studies, 2020)
This paper aims to scrutinize how Indonesian religious education, particularly the 2013 curriculum of junior high schools (7-9-year-old), has addressed environmental issues in its concepts or practices. In the Indonesian context, Education for Sustainable Development (ESD) has been implemented since 2009, and it ideally should be integrative in the curriculum. Religious education as the core of the national curriculum has pivotal roles in guiding students on how to be good people. In line with the ESD vision in preserving this Earth, a religious education curriculum has visions similar to the ESD. Therefore, this research reviewed the religious education curriculum literature and conducted an in-depth interview with five religious education teachers. Its results conveyed that the ESD values have existed within the religious education curriculum. However, practically it is less effective because the curriculum tends to focus on cognitive goals. In addition, more training is necessary to increase teachers’ capacity.